A new hybrid cycloconverter with smooth output voltage generation capability and accurate control of the circulating current - Klumpner, Christian; Xu, Tianning; Clare, Jon (2006)
Nowadays, power electronic converters based exclusively on IGBTs deliver excellent load side performance up to megawatt powers in the low voltage range (200-690V) and are steadily gaining performance in the medium voltage range as well. However, the medium and high voltage/high power range remains dominated by converters using naturally commutated thyristors (i.e. cycloconverters, current source inverters), which offer poorer output side performance. This paper proposes a new hybrid arrangement, targeting the medium and high-power range, comprising a naturally commutated cycloconverter connected to a PWM Voltage Source Inverter, able to offer improved output voltage quality and accurate control of the circulating current. The feasibility of the newly proposed concept is validated by Saber simulation results.